FcγRIV deletion reveals its central role for IgG2a and IgG2b activity in vivo. - Nimmerjahn, Falk; Lux, Anja; Albert, Heike; Woigk, Melissa; Lehmann, Christian; Dudziak, Diana; Smith, Patrick; Ravetch, J. V. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cellular Fcγ receptors are essential for IgG-dependent effector functions in vivo. There is convincing evidence that selective activating Fcγ receptors are responsible for the activity of individual IgG subclasses. Thus, IgG1 activity is absent in FcγRIII-deficient mice, and several studies suggest that the activity of the most potent IgG subclasses, IgG2a and IgG2b, might be dependent on either individual or a combination of activating FcγRs. To study the role of individual activating FcγRs for IgG subclass activity, we generated an FcγRIV-deficient mouse and showed that a variety of IgG2a- and IgG2b-dependent effector functions are impaired in the absence of this activating Fc receptor in models of autoimmunity and antibody-dependent cellular cytotoxicity.